Studying the reality of sports professionalism on the development of Iraqi football from the point of view of sports intellectuals - Yaseen Ali Khalaf (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Sports in our current era have witnessed a great development in the lives of people and for various activities, events, ages, and genders, and have become of great importance to countries and governments through the establishment of huge sports facilities for practice, marketing, and investment, thus transforming it into a sports industry managed by international sports companies. The aim of the research is to identify the reality of sports professionalism in the development of Iraqi football from the point of view of sports intellectuals. The researcher used a descriptive approach for its suitability and the nature of the research problem. The research community was represented by (1200) individuals from sports intellectuals, while the research sample consisted of (800) individuals, i.e. (400) individuals were excluded due to incomplete answers. It was divided into a survey sample (50) individuals, a construction sample (350) individuals, and an application sample (400). The results of the tables showed the total degree of answers of the sample members on all areas of the scale, and despite the different names and functions of the research sample, their results were close. These results indicate that all members of the application sample had a positive outlook and full awareness of a high degree towards the legal texts of sports professionalism and its importance in works to improve the good of Iraqi football clubs. The researcher concluded that the scale proved its effectiveness in measuring sports professionalism on the development of football from the point of view of sports intellectuals. The application of regulations and laws in a good and effective manner helped to provide the best for sports professionalism.